The rising of dawn - an investigation of the spatial and religious background of "dawn" in Psalm 139:7-12 - Sutton, L. (Journal for Semitics, 2011)
This paper focuses on the meaning of shahar ( ) in Psalm 139:7-12. A comparison will be made between Psalm 139:7-12 in the Old Testament and mythological imagery in the ancient Near East to get a better understanding of the religious background of shahar in this text. The investigation of the religious background of "dawn" helps to understand how the negative feeling of the one praying in Psalm 139 is transformed into positive imagery. Like the flying deity Shahar, YHWH is not bound to one realm, emphasizing that one cannot hide from YHWH. The same image can be used for the one praying in Psalm 139. Using spatial orientation in Psalm 139:7-12, the idea is further illustrated by concluding that God is present in all the realms. Ancient Near Eastern vertical and horizontal orientation will be utilised to illustrate how the focus in the psalm falls upon YHWH's omnipresence.
free